Chondroid Syringoma of the Medial Canthus. (11th March 2014) - Paraskevopoulos, Konstantinos; Cheva, Angeliki; Koloutsos, Giorgos; Matzarakis, Ioannis; Vahtsevanos, Kostas
Abstract : Chondroid syringoma, or pleomorphic adenoma of the skin, is a rare, benign skin adnexal tumor. It is usually exhibited as a slowly growing intradermal or subcutaneous nodule, typically located in the head and neck region. Because of the unremarkable clinical symptomatology of this rare tumor, the diagnosis is exclusively made retrospectively based on histological confirmation of the surgically excised tumor. We present a rare case of a chondroid syringoma located in the left medial canthus of a 58-year-old man. The patient had no symptoms and decided to excise it for cosmetic reasons only. Local excision with a macroscopic wide cuff of normal tissue was done, without destroying the aesthetic and functional structures, since the defect was restored by a finger flap. One year postoperatively, the patient has remained disease-free. Chondroid syringoma usually appears in the face but the location in the medial canthus is not mentioned in the literature for the last twenty years.